2010
DOI: 10.4161/epi.5.5.11929
|View full text |Cite
|
Sign up to set email alerts
|

Id1 overexpression is independent of repression and epigenetic silencing of tumor suppressor genes in melanoma

Abstract: The full molecular consequences of oncogene activation during tumorigenesis are not well understood, but several studies have recently linked oncogene activation to epigenetic silencing of specific genes.1,2 Transcriptional repressor Id1 is overexpressed in many malignancies including melanoma, and Id1 targets include tumor suppressor genes TSP1, CDKN2A (p16) and CDKN1A (p21), which are frequently epigenetically silenced in cancer. We confirmed that both TSP1 and CDKN2A have abnormal promoter region DNa methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Megan. A. Healey 11 reported a 13% and 20% methylation of TSP1 in their study on primary melanoma and melanoma cell lines respectively. A 10 and 7% methylation was observed in esophageal squamous cell carcinoma and pancreatic adenocarcinoma respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Megan. A. Healey 11 reported a 13% and 20% methylation of TSP1 in their study on primary melanoma and melanoma cell lines respectively. A 10 and 7% methylation was observed in esophageal squamous cell carcinoma and pancreatic adenocarcinoma respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Primers were designed to amplify the DNA template irrespective of the methylation status as previously mentioned. 11 The PCR product from the first step was diluted 10-folds and used as template for the second step where primers were designed to specifically amplify the methylated and the unmethylated regions of the TSP1 promoter. CpG Methylated HeLa Genomic DNA (New England Biolabs, USA) was used as a positive control for methylated allele and DNA obtained from the of normal ovary samples served as negative control.…”
Section: Methylation Specific Pcrmentioning
confidence: 99%
“…These transitional forms are called hybrid epithelial/mesenchymal phenotype (Jolly et al, 2015). It was also noted that stable lentiviral ID1 overexpression producing functional protein in melanoma cells failed to affect transcription/translation of the ID1 target genes suggesting that ID1 expression alone is insufficient to determine cell fate (Healey et al, 2010). Thus, it may be assumed that specific response triggered by ID1 depends on molecular context in the cancer cell or its environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that Id1 can inhibit cell apoptosis and promote angiogenesis by activating nuclear factor kappa B (NF-kappa B)/survivin-related signaling pathway, and ultimately promote the proliferation of a variety of cancer cells 1519. NF-kappa B can regulate the expression of survivin, which is a new member of the inhibitor of apoptosis protein (IAP) family.…”
Section: Introductionmentioning
confidence: 99%